2011
DOI: 10.1007/s10334-011-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy as a tool for in vivo determination of steatosis in liver transplant recipients

Abstract: Significant correlation was found between the results of histology and 1H MRS measurement of liver fat content. The method is suitable for non-invasive repetitive examination of liver fat in liver-transplants patients between protocol biopsies and for the screening of steatosis in other liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 26 publications
3
31
1
Order By: Relevance
“…Nevertheless, liver fat is not equally distributed within liver and different "within liver" variability has been reported. Hájek et al [14] showed that HFF obtained in three different positions varied by 20% in a group of 77 liver-transplant recipients. Van Werven et al [12] reported regional differences in HFF up to 3.5% and CV=14% in the study of 12 subjects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, liver fat is not equally distributed within liver and different "within liver" variability has been reported. Hájek et al [14] showed that HFF obtained in three different positions varied by 20% in a group of 77 liver-transplant recipients. Van Werven et al [12] reported regional differences in HFF up to 3.5% and CV=14% in the study of 12 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Correction for T1 relaxation can be avoided by long TR. A number of studies [9,12,14,[19][20][21] used average T2 values to correct for all patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations